Неравенства для внутренних радиусов неналегающих областей - Бахтин, А.К.; Вьюн, В.Е.; Трохимчук, Ю.Ю. (Видавничий дім "Академперіодика" НАН України, 2007)
This article is devoted to solving the new extremal problems on non-overlapping domains with free poles on rays and to the generalization of some results known before.